Pengaruh health risk dan trust terhadap intention to recommend pesan antar makanan dari restoran Padang - Melani Wahyu Diatri; Yulia Hendri Yeni (Universitas Negeri Padang, 2021)
This study aims to get other people to recommend purchasing at Padang Restaurants by not eating in place as a way to reduce the transmission of the Covid-19 Virus. Investigating and knowing the effect of health risk on the intention to recommend Padang restaurants in Sumatra during the Covid-19 Pandemic with trust mediation. The method reseach used is quantitative analysis and SEM analysis with Smart PLS 3.0 (PLS-SEM) was used as an analysis approach. This research uses descriptive survey and explanatory survey methods. The type of investigation carried out is a causal type. In this study using time horizon is a cross section/one shot. Data were collected using an online survey method. The research object chosen is people who already have income in Sumatra. The sampling technique used was purposive sampling. The sample size for this study was 170 respondents. The finding of this study show that; (1) health risk has a positive and not significant effect on trust, (2) health risk has a positive and significant effect on intention to recommend, (3) trust has a positive and significant effect on intention to recommend, (4) trust doesn’t mediate relationship between health risk and intention to recommendTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//